A novel surgical approach for en-bloc resection laparoscopic total pancreatectomy - Cai, Yunqiang (Medicine (Baltimore), 2020)
Laparoscopic total pancreatectomy (LTP) is technical challenging and rarely reported in the literature. Herein, we introduced a safe and feasible approach to perform LTP basing on our own experience. Over the period of July 2015 to August 2018, we performed 13 cases of LTP at our institution. Demographic characteristics, intraoperative and postoperative variables, and follow-up outcomes were prospectively collected. The surgical procedures were also described in this study. Seven male and six female patients were included in this study. The median age of the patients was 51 years (range 29–79 years). The median operative time was 355 minutes (range 300–470 minutes). The median estimated blood loss was 200 mL (range 50–1000 mL). The median postoperative hospital stay was 17 days (range 12–23 days). One patient suffered from bile leakage and another patient suffered from delayed gastric emptying. Both patients cured with conservative therapy. Laparoscopic total pancreatectomy can be safely and feasibly performed in well-selected patients.